2023
DOI: 10.3389/fcimb.2023.1257683
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1-3 inhibition increases SARS-CoV-2 replication and productive infection in lung mesothelial and epithelial cells

Flavia Trionfetti,
Tonino Alonzi,
Giulio Bontempi
et al.

Abstract: BackgroundDespite the significant progress achieved in understanding the pathology and clinical management of SARS-CoV-2 infection, still pathogenic and clinical issues need to be clarified. Treatment with modulators of epigenetic targets, i.e., epidrugs, is a current therapeutic option in several cancers and could represent an approach in the therapy of viral diseases.ResultsAim of this study was the analysis of the role of histone deacetylase (HDAC) inhibition in the modulation of SARS-CoV-2 infection of mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The reduced levels of CXCL10 were explained by the control exerted by both the type I IFN and IFN-γ pathways on the expression of this chemokine in fibroblasts ( Ohta et al., 2014 ; Yu et al., 2020 ). Besides inhibiting type I response, MS-275 was recently demonstrated to favor SARS-CoV-2 infection in MCs by modulating ACE2 and TMPRSS2 expression ( Trionfetti et al., 2023a ). Overall, these results strongly suggest that treatment with HDAC1-3 inhibitor MS-275 may favor viral infection by multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced levels of CXCL10 were explained by the control exerted by both the type I IFN and IFN-γ pathways on the expression of this chemokine in fibroblasts ( Ohta et al., 2014 ; Yu et al., 2020 ). Besides inhibiting type I response, MS-275 was recently demonstrated to favor SARS-CoV-2 infection in MCs by modulating ACE2 and TMPRSS2 expression ( Trionfetti et al., 2023a ). Overall, these results strongly suggest that treatment with HDAC1-3 inhibitor MS-275 may favor viral infection by multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several reports demonstrated that HDACs are implicated in the pathogenesis of viral infections ( Herbein and Wendling, 2010 ; Panella et al., 2016 ; Trionfetti et al., 2023a ). Lipopolysaccharide (LPS) stimulation was demonstrated to enhance HDAC3 activity, leading to tumor necrosis factor-α (TNF-α) production ( Zhu et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, HDAC6 inhibitors were found to reduce cytokine release, decrease T cell exhaustion, and contribute to innate immune cell memory processes, potentially providing therapeutic benefits in severe COVID-19 cases. On the other hand, a study exploring how HDAC inhibition affects SARS-CoV-2 infection in mesothelial cells revealed that blocking HDAC1-3 actually boosts SARS-CoV-2 cell entry, replication, and production [ 50 ]. Additionally, another investigation on a different RNA virus, influenza A virus, showed that suppressing HDAC6 activity leads to an elevated virus titer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, the key implication drawn is the necessity for a precise understanding and control of HDAC. While most drugs targeting HDAC have functioned as inhibitors, concentrating on pathological conditions where gene overexpression is a therapeutic target [ 53 , 54 ], our findings reveal that HDAC can contribute positively to the immune response at suitable expression levels, and inhibition might be detrimental [ 50 , 51 ]. This emphasizes the significance of delving into and managing the appropriate expression level and emphasizes the requirement for a precise comprehension of each specific class of HDAC, given its pervasive impact on the entire body.…”
Section: Discussionmentioning
confidence: 99%